KINERJA DALAM PELAYANAN PUBLIK DI KANTOR KELURAHAN TANUNTUNG KECAMATAN HERLANG KABUPATEN BULUKUMBA - Risnawati, Risnawati; Mone, Ansyari; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The purpose of this research is to find out the "Effectiveness of Employee Performance in Public Services at the Village Office, Herlang District, Bulukumba Regency". The type of research used in this research is descriptive research with qualitative methods. The data collection techniques include observation, interviews and documentation. The results of this research show that "Employee Performance in Public Services at the Tanuntung Subdistrict Office" has received satisfaction from the community and is also quite effective. This can be seen in terms of the quality of their employees who have the level of knowledge and skills used during the service process, which makes work easier and people also feel satisfied with the services provided. Not only the quality, the quantity of employees at the Tanuntung Subdistrict office is also quite effective, where the amount of work produced is quite maximum and in accordance with the planned targets, even though at the service process stage there are problems in the facilities.